Effect of different feeding levels of turmeric and amla on performance of broilers - A.V. RATHOD and S.K. PANDEY, GYAN CHANDRA S.H. MANE, S.A. DHAGE (Indian Journal of Animal Production and Management, 2020)
An experiment was conducted with two types of herbal products (amla and turmeric) either alone or incombination in seven dietary treatments to study the growth performance in broilers. The treatment groupsconsisted of control (T0), 0.25% turmeric (T1), 0.5% turmeric (T2), 0.25% amla (T3), 0.5% turmeric (T4),0.25% turmeric+amla (T5) and 0.5% turmeric+amla (T6) were included in broiler diet. The different types ofherbals feed supplement either alone or in combination at 0.25% and 0.5% levels in broiler diet give bettergrowth performance of body weight gain or feed conversion ratio. The feed conversion ratio increasedwhich were significant in broilers fed with different herbals either alone or in combination compared tocontrol. The results suggested that herbals like amla and turmeric can be supplemented in broiler feeds asthey have direct effect on improving body weight gain, feed conversion ratio and better economic return.